Free Speech and Academic Freedom in the Era of the Alt-Right - Hackett, Robin; Rivera, Javier (Radical Teacher, 2020)
This essay is written in two parts: "The Weaponization of Free Speech," describes a series of events on a university campus. The narrative clarifies the nature of current right wing attacks on personnel and programs in women, gender, and sexuality studies, and in race and ethnic studies. "An Annotated Bibliography on Academic Freedom" collects and describes materials that can assist campus communities in building cultures of resistance and resilience in the face of these attacks.